Option valuation and accounting for contingent consideration in mineral sector acquisitions - Chandra, A.; Guj, Pietro (Edith Cowan University, 2012)
Vendor consideration on acquisition of mineral sector companies/projects may include shares and/or options contingent on achievement of uncertain milestones either financial (specified levels of future profit, share price etc) or physical (delineation of specific levels of mineral resources). Accounting standards on business combination, fair value and financial instruments have recently undergone major changes, with potentially significant impact on the valuation and accounting of the consideration transferred. The valuation approaches to assess the "fair value" of contingent consideration in the form of financial instruments include expected present value techniques and option-pricing models. These are discussed and applied to an actual acquisition of an iron ore exploration project/company in West Africa. Valuation of contingent consideration provides valuable insights and benefits while negotiating and accounting for business acquisitions.